KETIMPANGAN AKSES TERHADAP KEADILAN: PERSPEKTIF SOSIOLOGI HUKUM TERHADAP MASYARAKAT MARGINAL - Arrasyid Wiriadihardja, Mochamad Keizar (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
The unequal access to justice faced by marginalized groups is examined in this article from the perspective of legal sociology. Qualitative, normative, and empirical methods are used in this article to examine the institutional, cultural, and structural elements that lead to legal injustice. The study shows that despite the existence of a formal legal system, marginalized groups often face obstacles, including lack of legal literacy, prejudice, and costs. This article advocates for social justice-based strategies and inclusive legal policy change.